The effect of physical cleansing on moral judgment and moral behavior among undergraduate students - Choo, Jia Sheng; Lee, Xiao Si (2019)
Physical cleansing can be simply known as the act of cleansing oneself. Previous literature suggested that there has been a psychological association between physical purity and moral purity. However, previous studies had provided different contradict results in suggesting the effect of physical cleansing on moral psychology from different perspectives. To clear the doubts, this current experimental study aims to clarify the effect of physical cleansing action on moral judgment and immoral behavior among undergraduates in Malaysia. With the utilization of an experimental design and a between-subjects research design, the difference between hand wiping and non-hand wiping condition had been clearly tested. 40 participants who were unknown of the nature of the study were recruited through purposive sampling method. Two tasks were given to the participants in order to measure moral judgment and cheating behavior. The order of the experimental tasks were counterbalanced to maximize the control over sequential effects. The two independent sample t-tests has found that there is no significant difference between physical cleansing and moral judgment. Furthermore, there is also a nonsignificant effect found for physical cleansing and immoral behavior. In addition, there is also no gender differences in moral judgment and immoral behavior. The underlying determinants of the results could be due to the differences of participants’ response effort, research settings, and the amount of incentives. These determinants could affect the participants’ motivation to conduct immoral behaviors such as cheating. The findings of the current research could help in contributing to the literature of the effect of physical cleansing on moral psychology. Therefore, future research should take participants’ response effort into account to reduce the profound effect caused by low motivation in generating moral judgment, and conducting immoral behavior.